Inclusion of Children with Disabilities from the Palestinian-Arab Community in the Israeli Education System - Majadley, Enas (Rocznik Pedagogiczny, 2020)
The concept of inclusion is implemented in Israeli educational system with introduction of 1988 Special Education Law (SEL). The political, socio-cultural and economical changes improved the general status of people with disabilities in the Arab and Jewish communities. However, the Jewish education system, and the Arab education system in general differ, that applies also to the issue of special needs education. Students with disabilities representing minority groups suffer from addi- tional barriers. The main aim of the article is to discuss the issue of integrating students with disabilities into general education in Arab schools in Israel. The situation of children with special educational needs (mainly with intellectual disabilities) in educational system in Israel is discussed, with focus on children from Palestinian-Arab community. The Arab teachers attitudes and behaviors toward the inclusion and disability are analyzed. Although, the research within the topic is limited, the available results indicate rather negative attitudes of Arab teachers towards disabilities. This state might be partly embedded within the socio-cultural context. The further research within the topic is necessary.